Can you stop a volcanic disaster? - Doeden, Matt (You choose. Interactive eco adventure., 2021)
"The ground is shaking. A volcano is about the erupt. Hundreds of lives are in danger. But you can help! Navigate through three different stories to discover what is happening below Earth's surface. With dozens of story outcomes, it's up to you to stop a volcanic disaster. The planet needs you. Will YOU CHOOSE to help?"--Provided by publisher.